Speak with confidence : overcome self-doubt, communicate clearly, and inspire your audience - Acker, Mike (John Wiley & Sons, Inc., 2023)
"Public speaking is a 'universal advantage'--a skill that gives you a leg up in nearly any profession or situation--and the single greatest requirement for great speaking is confidence. When you learn to communicate with confidence, it bleeds over into every area. Because this book utilizes a wholistic approach that addresses the entire person and not just exterior skills, your confidence on stage will follow you off stage"--